Improving thermal comfort in the urban landscape of housing communities in tropical climate: A case study of Bang Chalong Community, Thailand - Janpathompong, Shusak; Chatakul, Paron (International Journal of Building, Urban, Interior and Landscape Technology, 2022)
In developing countries, low-income housings seem to sacrifice quality over quantity. For a tropical country such as Thailand, where the temperature remains consistently high throughout the year, thermal comfort impacts living quality, especially in urban areas. Bang Chalong Community is a cluster of densely arranged mid-rise apartments in Samut Prakan, the peri-urban area of Bangkok, chosen by the NHA (National Housing Authority) to improve its living quality as a pilot project. While current literature investigates and explores solutions to mitigate thermal comfort in buildings, few studies focus on outdoor areas adjacent to buildings. This research aims to assess the outdoor hot-spot of the community, proposes appropriate attributes and design approaches to improve urban landscape elements leading to comfortable conditions, and recommends landscape design strategies for similar future development. The thermal condition was conducted using the Wet Bulb Globe Temperature (WBGT) data logger on 25 locations. The ambient temperature (TG) was used as the indicator for thermal comfort. It is found that critical attributes affecting the thermal condition are 1) the type of surfaces – hardscape or soft scape, and 2) the amount of surface and time exposed to solar energy – shade or sunlight. The thermal comfort improvement, including potential uses by landscape design, was proposed under four strategies; shading, added green, orientation & ventilation, and functional refinement. They are recommended to create suitable thermal comfort by landscape design for future development of a similar type